2012
DOI: 10.1080/13614568.2012.746740
|View full text |Cite
|
Sign up to set email alerts
|

Deviant bodies, stigmatized identities, and racist acts: examining the experiences of African-American gamers in Xbox Live

Abstract: The purpose of this article is to illustrate how minority gamers, particularly AfricanAmerican males, are subject to the label of deviant within the virtual gaming community of Xbox Live. They are labeled deviant based on the stigma of their physical identity Á blackness, through a process of linguistic profiling. By employing virtual ethnography, the author identifies a process that leads to racism based on how the black gamer sounds within the space. The act of racism emerges through a process involving ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 20 publications
6
101
0
2
Order By: Relevance
“…Women are typically perceived as a minority in online gaming spaces, and the research has consistently suggested that they often experience general and sexual harassment from other players (Ballard and Welch 2017;Chess and Shaw 2015;Fox and Tang 2014;Gray 2012;Salter and Blodgett 2012). The recent survey of Fox and Yeng Tang (2017) on women's experience with online videogames found this often led to rumination about the harassment, perceptions of organisational unresponsiveness to issues, and withdrawal from the game.…”
Section: Female Gaming Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are typically perceived as a minority in online gaming spaces, and the research has consistently suggested that they often experience general and sexual harassment from other players (Ballard and Welch 2017;Chess and Shaw 2015;Fox and Tang 2014;Gray 2012;Salter and Blodgett 2012). The recent survey of Fox and Yeng Tang (2017) on women's experience with online videogames found this often led to rumination about the harassment, perceptions of organisational unresponsiveness to issues, and withdrawal from the game.…”
Section: Female Gaming Researchmentioning
confidence: 99%
“…Using statements designed to be neutral and inoffensive, female voices were found to receive considerably more negative reactions, resulting in three times more negative comments than male voices. Gray (2012) found that linguistic profiling was common in online gaming. Players reported frequent derision and harassment, typically featuring sexist, racist, nativist, and heterosexist language once they started communicating verbally with other players.…”
Section: Female Gaming Researchmentioning
confidence: 99%
“…When I consider the research being undertaken by younger scholars of color today, I am impressed by the kinds of unique information that they are adding to our literature. Who else would give attention to explicating the role of Black Child Savers in the early juvenile court movement (Ward, ); violence and other offending among girls of color (Jones, ); race and deviance in online communities (Gray, , ); the views and roles of officers of color in how minority communities are policed (Brunson and Gau, ; Owusu‐Bempah, ); the consequences for minority youths of policing the paths to school (Rios, ; Shedd, ); how the racial divide operates in the context of local jails (Walker, ); guilt by association of law‐abiding youth (Durán, ; Rios, ); racial/ethnic politics and consequences of enforcing immigration policies (Macias‐Rojas, ; Zatz and Rodriguez, ); guilt by association of documented immigrants and U.S. Latino citizens (Armenta, ); and the like.…”
Section: Take Stock Of How Race/ethnicity and Crime/justice Are Relatedmentioning
confidence: 99%
“…Who else would give attention to explicating the role of Black Child Savers in the early juvenile court movement (Ward, 2012); violence and other offending among girls of color (Jones, 2009); race and deviance in online communities (Gray, 2012(Gray, , 2014; the views and roles of officers of color in how minority communities are policed (Brunson and Gau, 2015;Owusu-Bempah, 2015); the consequences for minority youths of policing the paths to school (Rios, 2011;Shedd, 2015); how the racial divide operates in the context of local jails (Walker, 2016); guilt by association of law-abiding youth (Durán, 2013;Rios, 2011); racial/ethnic politics and consequences of enforcing immigration policies (Macias-Rojas, 2016;Zatz and Rodriguez, 2015); guilt by association of documented immigrants and U.S. Latino citizens (Armenta, 2017); and the like. Upon seeing this list, some will complain that the work of some of the scholars noted is not "rigorous" enough for mainstream criminology, signaling that it is not quantitative.…”
Section: Be Inclusive: Bring the Full Array Of Diverse Perspectives mentioning
confidence: 99%
“…This lack of workplace diversity is reflected in research on enrolment and participation in domestic game culture, public events and game content and the highly contextual meanings of being a gamer (Thornham, 2008;Shaw, 2012;Taylor et al, 2009). Some online game cultures have been found to have highly gendered, raced and heteronormative cultures (Jenson and de Castell, 2015;Gray, 2012). It is within this context that we must understand the development of community management as an occupation.…”
Section: The Games Industry As Cultural and Creative Industrymentioning
confidence: 99%